The Romanians struggle for unification - 1834-1849. Transl. from the Romanian, by L. Teodoreanu (Academy of the Socialist Republic of Romania, 1970)
With ills, index and prts. Original title: Lupta Românilor pentru unitatea naţională 1834-1849.